Alumina membrane coated activated carbon: a novel strategy to enhance the mechanical properties of a solid catalyst. Issue 13 (26th January 2016) - Cheng, Dang-guo; Jin, Weiyang; Zhan, Xiaoli; Chen, Fengqiu
Abstract : A novel strategy is described to enhance mechanical properties of solid catalyst by coating a thin layer of alumina membrane on activated carbon particles. This method can make the attrition index of activated carbon decrease significantly. Abstract : This paper presents a novel strategy to enhance the mechanical properties of a solid catalyst. By employing a slip-casting method, an alumina membrane can be prepared on the surface of activated carbon particles uniformly. Significantly, the mechanical properties test indicates that the attrition index of activated carbon decreases from 12.6% to 2.9% due to the alumina membrane coating.